2006
DOI: 10.1126/science.1134388
|View full text |Cite
|
Sign up to set email alerts
|

Solid-State Qubits with Current-Controlled Coupling

Abstract: The ability to switch the coupling between quantum bits (qubits) on and off is essential for implementing many quantum-computing algorithms. We demonstrated such control with two flux qubits coupled together through their mutual inductances and through the dc superconducting quantum interference device (SQUID) that reads out their magnetic flux states. A bias current applied to the SQUID in the zero-voltage state induced a change in the dynamic inductance, reducing the coupling energy controllably to zero and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
204
1
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 206 publications
(206 citation statements)
references
References 24 publications
0
204
1
1
Order By: Relevance
“…
Superconducting circuits are promising candidates for constructing quantum bits (qubits) in a quantum computer; single-qubit operations are now routine 1,2 , and several examples 3,4,5,6,7,8,9 of two qubit interactions and gates having been demonstrated. These experiments show that two nearby qubits can be readily coupled with local interactions.
…”
mentioning
confidence: 99%
“…
Superconducting circuits are promising candidates for constructing quantum bits (qubits) in a quantum computer; single-qubit operations are now routine 1,2 , and several examples 3,4,5,6,7,8,9 of two qubit interactions and gates having been demonstrated. These experiments show that two nearby qubits can be readily coupled with local interactions.
…”
mentioning
confidence: 99%
“…5 We also considered two more models: ͑i͒ For N qubits inductively coupled without any connecting loop, multiplequbit interactions are intrinsically involved but their strengths are very weak, as for instance of N =4, J zzzz ͑4͒ Ϸ 10 −6 J zz00 ͑2͒ in the parameters of Ref. 12. If the two-qubit interactions are much stronger than other multiple-qubit interactions, H N Ϸ͚ iϽj H 2 ͑ij͒ .…”
Section: ͑10͒mentioning
confidence: 99%
“…Especially, coherent manipulation of quantum states in tunable superconducting devices has enabled to demonstrate macroscopic qubits [6][7][8] and entangled states of qubits. [9][10][11] Experimentally, it has been shown that, in terms of pseudospins, different types of exchange interactions between two artificial spins such as an Ising interaction for charge qubits 9 and flux qubits 10,12 and an XY interaction for phase qubits 11 can be realized and controlled by the system parameters. Although different types of solid-state qubit systems have revealed such artificial-spin exchange interactions, multiple artificial-spin interactions have not been demonstrated yet.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Superconducting qubits utilize charge [5][6][7] or flux [8] degrees of freedom, or energy levels quantization in a single current-biased Josephson junction [9,10]. Inter-qubit coupling [15][16][17][18][19][20] and also quantum logic gates [21][22][23] have been reported later. Further progress in the field slowed down due to obvious decoherence issues that are still to be overcome in order to implement a working quantum computer.…”
mentioning
confidence: 99%